Harnessing the Power of Educational Games to Enhance Engagement and Motivation among Young Language Learners - Azizi, Neshat; Khalid, Sadaf; Podpera, Rastislav; Karimovna, Yorova Sayora; Hornáček Banášová, Monika; Szabó, Erzsébet (Journal of Education Culture and Society, 2026)
Aim. This study aims to investigate how games, as an enjoyable teaching method, can enhance motivation and engagement among young learners. It explores how different aspects of motivation and engagement manifest within a game-based instructional setting. Methods. Using a qualitative approach, the study conducted a case analysis with a randomly selected class of 15 children from a language institute. Data was gathered over two months through video recordings, teacher journals, and classroom observations. Results. The results indicate that learning through games creates an enjoyable environment that significantly boosts learners’ motivation and engagement. Teacher journals, and observation notes revealed that children participated enthusiastically in every lesson and showed high motivation throughout the sessions. These findings align with previous research demonstrating that educational games foster intrinsic motivation and active participation among language learners. Furthermore, games help reduce anxiety and promote positive attitudes towards language learning. Conclusions. Therefore, the findings suggest that game-based instruction serves as an effective motivator and engager, particularly in the early stages of the learning process, contributing positively to learner autonomy and sustained interest in language acquisition. Future studies could explore longitudinal impacts and game design features that maximize motivational benefits.